Motivational and value component of professional and personal readiness of future defectologists - Svetlana N. Sorokoumova; Elvira N. Larikova (Russian Journal of Education and Psychology, 2025)
Background. The article describes some psychological features of the structure of personal readiness of future defectologists to professional activity. The article analyses the results of the establishing experiment, the participants of which were students of FSBEI VO ‘Nizhny Novgorod State Pedagogical University named after Kozma Minin’.